If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 + -5x = 24 + 3x Solving -16 + -5x = 24 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -16 + -5x + -3x = 24 + 3x + -3x Combine like terms: -5x + -3x = -8x -16 + -8x = 24 + 3x + -3x Combine like terms: 3x + -3x = 0 -16 + -8x = 24 + 0 -16 + -8x = 24 Add '16' to each side of the equation. -16 + 16 + -8x = 24 + 16 Combine like terms: -16 + 16 = 0 0 + -8x = 24 + 16 -8x = 24 + 16 Combine like terms: 24 + 16 = 40 -8x = 40 Divide each side by '-8'. x = -5 Simplifying x = -5
| 16y^2x^2+24yx^2+9x^2=0 | | 3+2s-2=7s+9-4s | | 15x=3x^2+5x-28 | | y=-2/7-5 | | -5x+3(6+x)=34 | | 2(y-33)+3(y-2)=8 | | r-3=4+2 | | (9x-8)-(2x-2)= | | -2/3+1/2=x | | 4x-y=-8 | | -2x^2-7x=0 | | -2/3+1/2= | | (-7x+5)(-5x^2+7x-3)= | | x^5-3x^4-23x^3+51x^2+94x-120=0 | | 9x+9y=15 | | 5(3x+7)-1=3(5x+k)+4 | | 2(2z+2)-8= | | 15x=3x^2-28 | | 2x-4(5x+3)-(3x-7)=9x | | 5x+13=-17 | | 4x^6+9x^3-28=0 | | 9n-63=2n-18 | | 2y+-8=8 | | 45-50-(-12)= | | u-4u=3 | | 5-20=-7 | | 7r+10=3r+15 | | 12b-8(2b-3)=16 | | 60x^4-89x^3+2x^2+23x+4=0 | | 1/2(x-10)+4=5 | | 7n-8=-29 | | 6x^4-81x^2+162=0 |